DAYA PREDASI IKAN PEMAKAN JENTIK NYAMUK Aedes Sp SEBAGAI SUMBER BELAJAR UNTUK MENYUSUN PANDUAN PRAKTIKUM BIOLOGI SMA - Handoko Santoso; Agus Sutanto; Nurhat Alamsyah; Suharno Zen (UNIVERSITAS MUHAMMADIYAH METRO, 2022)
Mosquitoes are vectors of various diseases such as malaria, DHF, and elephantiasis. Many attempts have been made to suppress the mosquito population, one of which is biological control using mosquito larvae. The purpose of this study was to determine the predation power of the Aedes sp larvae. This type of research is descriptive. The data obtained are presented in tabular form and analyzed descriptively. The results showed that the predation power of betta fish (Betta splendens) was higher (80 larvae / 24 hours) compared to guppy fish (Poecillia reticullata) with 52 larvae / 24 hours and black molly fish (Poecillia splendens) with 42 larvae / 24 hours. The results of the study were validated by design experts and material experts with a percentage of 71.24% (good criteria) and compiled as a source of learning in the form of biology practical instructions for senior high school. Kata Kunci : Daya Predasi, Jentik nyamuk, sumber belajar biologi